Employed yet poor: low-wage employment and working poverty in South Africa. Issue 3 (3rd May 2020) - Feder, Jade; Yu, Derek
ABSTRACT: Working poverty exists worldwide and has shown an increase in prevalence over the past few decades. Over the years, there has been an increase in the number and severity of low-wage employment, which in turn contributes significantly to poverty. Whilst paid employment has generally been considered as the predominant means to survive financially, salaries may be too low to maintain reasonable living standards. South African research on low-wage employment and working poverty in particular, are rare. Using data from the first four waves of the National Income Dynamics Study, this study fills the existing research gap by examining low-wage employment, working poverty, and low-wage poverty. The empirical findings indicated that all three groups are predominantly lowly-educated, middle-aged African female employees involved in elementary occupations in the informal sector.